2011
DOI: 10.2106/jbjs.j.01350
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Comparison of the Incidence of Adverse Outcomes After Simultaneous-Bilateral and Staged-Bilateral Total Knee Arthroplasty

Abstract: Simultaneous-bilateral total knee arthroplasty was associated with a clinically important reduction in the incidence of periprosthetic joint infection and malfunction within one year after arthroplasty, but it was associated with a moderately higher risk of an adverse cardiovascular outcome within thirty days. If patients who are at higher risk for cardiovascular complications can be identified, simultaneous-bilateral knee arthroplasty may be the preferred surgical strategy for the remaining lower-risk patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 37 publications
10
94
2
Order By: Relevance
“…Prior research has shown that the overall incidence of procedure-related complications was lower after same-day compared to staged bilateral TKAs during a single hospitalization [18]. Likewise, a recent analysis [14] suggested, after risk adjustment, the odds of developing hematoma and infection were lower in patients undergoing same-day bilateral TKAs than in patients undergoing staged bilateral TKAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research has shown that the overall incidence of procedure-related complications was lower after same-day compared to staged bilateral TKAs during a single hospitalization [18]. Likewise, a recent analysis [14] suggested, after risk adjustment, the odds of developing hematoma and infection were lower in patients undergoing same-day bilateral TKAs than in patients undergoing staged bilateral TKAs.…”
Section: Discussionmentioning
confidence: 99%
“…Data have shown a decrease in 30-day mortality after sameday bilateral TKAs from 0.99% in 1990 [24] to 0.38% in 2007 [14]. However, despite potential advantages of the same-day approach, including exposure to the risks of anesthetic only once, one postoperative course of pain, reduced rehabilitation, and an earlier return to baseline function [10,11,23], the safety of same-day procedures has been questioned because of higher morbidity and mortality when compared with unilateral TKAs [15,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Patients undergoing bilateral joint arthroplasties were excluded because of greater complication rates and these patients were deemed not directly comparable to patients with cirrhosis undergoing unilateral joint arthroplasties [17,21]. Patients with different states of residence and hospitalization in the database were excluded because if complications were to occur, these patients may not return to the original state for treatment.…”
Section: Patient Selectionmentioning
confidence: 99%